PENGARUH CAMPURAN JENIS KAYU TERHADAP BEBERAPA SIFAT KAYU LAPIS*) - I M Sulastiningsih; Paribotro Sutjigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Experimental plywood (5 - piy) were made from 12 wood species veneers glued with urea formaldehyde. Thichness of veneer was 1.5 mm and the range of veneer density was 0.38 - 0.83 g/cm3. Veneers were divided into 3 groups based on their density, i.e. low, medium and high. The plywood properties were tested according to the American Standard (ASTM) and the Japannese Standard (JAS) included density. tensile strength. bending strength, compression strength, and moisture resistant bonding strength.The results revealed that plywood density was higher than veneer density (same wood species) or average veneer density (mixed wood species). Tested mechanical properties of plywood increased if the plywood density increased and the relationship could be expressed by linier regression equations. The tensile strength, bending strength and compression strength of plywood were tested both on parallel and perpendicular to face grain. Correlation coefficient of the relation-ship between plywood density and those plywood mechanical properties on parallel to face grain (r = 0.66 - 0.84) were higher than that on perpendiculor to face grain (r = 0.51 - 0. 74). Similar results were obtained with F calculated but all of them were highly significant. Based on those results it could be concluded that some mechanical properties of plywood could be estimated from its density, regardless of its wood species.